The Minsk ghetto, 1941 - 1943: Jewish resistance and Soviet internationalism - Epstein, Barbara Leslie (The S. Mark Taper Foundation imprint in Jewish studies, 2008)
Jewish-Byelorussian solidarity in World War II Minsk -- Why Minsk was different -- The Minsk ghetto -- The ghetto underground -- Solidarity in wartime Minsk -- Going to the partisans -- The Soviet betrayal of the Minsk underground -- Strategies of resistance elsewhere: the Kovno ghetto